Research on building a biochar production model from agricultural by-products in Gia Lai province - Thi Thanh Viet, Nguyen; Phuong Anh, Bui; Duc Hanh, Nguyen; Minh Huy, Le; Thanh Duy, Nguyen; The Doi, Bui; Thi Bich Lieu, Pham (Journal of Forestry Science and Technology, 2024)
ABSTRACT The impact of climate change on ecosystems and agricultural systems, particularly in key agricultural areas like the Central Highlands of Vietnam, has caused severe soil degradation, water depletion, and desertification, directly affecting productivity and livelihoods. Sustainable agricultural solutions, especially biochar, have gained attention due to their ability to improve soil fertility, retain moisture, and reduce greenhouse gas emissions. This research focuses on developing a biochar production model from agricultural by-products in Gia Lai to meet both domestic and export needs. Biochar was produced through the pyrolysis of coffee by-products, including stems, branches, and fruit husks. The study employs 10 brick kilns (90 m³ capacity) for stems and branches, and 15 steel kilns (300 kg/batch capacity) for fruit husks and leaves. The biochar produced meets export quality standards, with a fixed carbon content ≥70.0%, ash content ≤3.0%, and calorific value ≥7,000 Kcal/kg. Additionally, biochar is combined with the biological agent Trichoderma to produce 1,000 tons of organic microbial fertilizer, surpassing national standards for organic matter content (≥15%) and Trichoderma density (≥1.0x10⁶ CFU/g). Biochar production from agricultural waste not only reduces waste but also contributes to sustainable agriculture in the Central Highlands. The research results show great potential for expanding biochar production models, improving soil health, reducing farming costs, and increasing farmers' income.